Understanding the Relationship Between Coach and Athlete Perceptions of Training Intensity in Youth Sport. Issue 11 (November 2018) - Scantlebury, Sean; Till, Kevin; Sawczuk, Tom; Weakley, Jonathon; Jones, Ben
Abstract : Abstract: Scantlebury, S, Till, K, Sawczuk, T, Weakley, J, and Jones, B. Understanding the relationship between coach and athlete perceptions of training intensity in youth sport. J Strength Cond Res 32(11): 3239–3245, 2018—To alleviate issues arising from the over-/under-prescription of training load, coaches must ensure that desired athlete responses to training are being achieved. The present study aimed to assess the level of agreement between the coach-intended (presession) and observed (postsession) rating of perceived exertion (RPE), with athlete RPE during different training intensities (easy, moderate, hard). Coach-intended RPE was taken before all field-based training sessions over an 8-week in-season period. After training, all coaches and athletes, who were participants in hockey, netball, rugby, and soccer were asked to provide an RPE measure for the completed session. Sessions were then classified based on the coach's intended RPE, with a total of 28, 125, and 66 easy, moderate, and hard training sessions collected, respectively. A univariate analysis of variance was used to calculate within-participant correlations between coach-intended/-observed RPE and athlete RPE. Moderate correlations were found between coach-intended and athlete RPE for sessions intended to be moderate and hard whilst a small correlation was found for sessions intended to be easy. The level of agreement between coach and athlete RPE improved following training with coaches altering their RPE to align with those of the athlete. Despite this, moderate and small differences between coach-observed and athlete RPE persisted for sessions intended to be easy and moderate, respectively. Coaches should, therefore, incorporate strategies to monitor training load to increase the accuracy of training periodization and reduce potential over-/under-prescription of training.